Patterns of predation of Pink-footed Goose nests by polar bear - Prop, Jouke; Oudman, Thomas; van Spanje, Tom M.; Wolters, Eva H. (Ornis Norvegica, 2013)
This study explored patterns of predation by polar bear Ursus maritimus on the nests of Pink-footed Geese Anser brachyrhynchus on the coastal tundra stretch Nordenskiöldkysten, west coast of Spitsbergen, Svalbard. Goose nests occurred in densities of up to 126 nests/km2 (mean=6.4), at an average distance of 1.5 km from the seashore, and were mainly associated with greenstone outcrops. Open, flat areas were avoided for nesting. Goose pairs nested in colonies of up to 23 nests, with 50% of the pairs nesting in colonies larger than 5. In 2011 and 2012, polar bears invaded the Pink-footed Goose nesting area to consume goose eggs, a behaviour that they had not exhibited in previous years. Polar bears selectively visited the taller outcrops and locations with the larger number of goose nests. Moreover there was a steep gradient in predation from the seashore towards the inland, with no predation at distances greater than 1.8 km from the coastline. We expect that the predation pressure by polar bears will aggravate in the coming years when more bears learn to exploit the inland goose colonies.